Severe Hypersensitivity Reactions with Oral Manifestations: Case Reports on Stevens-Johnson Syndrome and DRESS Syndrome - Sura A. A. Fuoad Al-Bayati (Journal of Pharmacy and Bioallied Sciences)
Stevens-Johnson syndrome (SJS) and Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome are rare conditions, representing severe hypersensitivity reactions with significant oral presentations. SJS is an uncommon but severe variant of erythema multiforme, presenting skin and mucosal eruptions that can be potentially fatal. DRESS syndrome, similarly, involves a severe hypersensitivity reaction characterized by fever, rash, and organ involvement. DRESS syndrome is a rare but severe drug-induced hypersensitivity reaction characterized by fever, rash, eosinophilia, and internal organ involvement. The condition often presents with elevated liver enzymes and systemic symptoms that necessitate prompt diagnosis and treatment. This report discusses a case of DRESS syndrome in a 41-year-old patient, highlighting the clinical presentation, investigations, differential diagnosis, and treatment approach. Both conditions require prompt diagnosis and treatment, often involving hospitalization. This report discusses two cases of severe hypersensitivity reactions with oral manifestations.